Analysis of the Influence of Academic Parenting, Children’s Values, and Self-Concept on Motivation to Continue Higher Education in Students in Kawasan Industri Jababeka - Asyhar, Athaya Nadiya; Hastuti, Dwi; Riany, Yulina Eva (Jurnal Paedagogy, 2024)
This study aims to analyze the influence of academic parenting, children’s grades, and self-concept on motivation to continue higher education among high school and vocational high school students in Jababeka Industrial Estate, Bekasi Regency. This study used a quantitative approach with an explanatory design on 120 high school and vocational school students and 120 student guardians. The research instrument used a questionnaire and was analyzed by correlation and SEM tests. The results of this study indicated that the variables of academic parenting, self-concept, and motivation to continue education are in the medium category, while the variable of children’s values was in the low category. The results of the T-Test revealed that the motivation to continue their education of high school students was significantly different from vocational students; high school students had higher motivation. The correlation test between variables showed a significant positive relationship between academic parenting variables with self-concept and motivation to continue education. Influence analysis found a direct influence of academic parenting variables on self-concept and self-concept variables on motivation to continue education. The results of path analysis found that the academic parenting variable indirectly affects motivation to continue education, with the self-concept variable as a mediator. The implication of this research is to strengthen the self-concept of students in industrial areas through academic parenting and increase students’ motivation to continue their education by forming a positive self-concept.